It's the End of Globalization as We Know It! Zeitgemäße Betrachtungen zur politischen Ökonomik der Globalisierungskrise - Christian Reiner (Johannes Kepler University Linz, Institute for Comprehensive Analysis of the Economy (ICAE), 2022)
Finanz- und Wirtschaftskrise 2008/09, COVID-19-Pandemie, Ukrainekrieg und eine Reihe protektionistischer Politikmaßnahmen haben zu einer Abnahme der internationalen Arbeitsteilung geführt. Der Beitrag analysiert aus einer politökonomischen Perspektive Verteilungseffekte, Rodriks Trilemma, das Fehlen eines Hegemons sowie die mangelnde Attraktivität des Modells der Hyperglobalisierung für den globalen Süden als wesentliche Erklärungsfaktoren für die Globalisierungskrise. Ob zukünftig eine De- oder Re-Globalisierung dominieren wird, hängt neben politischen Machtverhältnissen nicht zuletzt von den ambivalenten Effekten von Digitalisierung und Klimawandel ab. – – The Great Recession in 2008/09, COVID-19 pandemic, the war in Ukraine and the proliferation of protectionist policies have resulted not only in a stagnation, but in a retreat of globalisation. This paper identifies four factors in order to understand the ultimate causes of the current crisis of globalisation: distributional effects, Rodrik's trilemma, the absence of a hegemon and the rejection of the logic of hyperglobalisation in the global South. Whether the future will be more or less globalised depends, beside political power, on the ambivalent effects and interplay of digitization and climate change.
Keywords: 330; Globalisierung; Politische Ökonomie; Rodriks Trilemma; Demokratie; Verteilung; Globalisation; political economy; Rodrik's trilemma; democracy; distribution